PERAN INSTAGRAM DALAM STRATEGI KOMUNIKASI PEMASARAN UNTUK MENINGKATKAN CITRA MEREK DONATELLO - Elsy Fitriyany (Communicative : Jurnal Dakwah dan Komunikasi, 2024)
This study examines the role of Instagram in the marketing communication strategy of Donatello, a local shoe brand in Indonesia, focusing on how it enhances the brand’s image. Using a qualitative approach and content analysis, the research analyzed posts, stories, and follower interactions from Donatello’s official Instagram account between June 1 and June 18, 2024. The analysis concentrated on key brand image elements such as associations, uniqueness, strengths, and favorability. The findings show that Donatello effectively leveraged Instagram to build strong brand associations, highlighting product quality, modern lifestyle, and unique shoe designs. Consistency in posting high-quality content and active engagement with followers has played a significant role in strengthening Donatello’s brand image, enabling the brand to stay relevant in a fast-evolving market. The study emphasizes that Instagram has been a key tool in shaping positive perceptions of quality and contemporary style, while also expanding Donatello’s market reach. This research underscores the importance of social media in reinforcing the brand image of local businesses, particularly in the face of global competition. The insights gained offer valuable guidance for other local brands seeking to enhance their image and competitiveness through effective social media strategies.